Activation-induced markers detect vaccine-specific CD4⁺ T cell responses not measured by assays conventionally used in clinical trials - Bowyer, G; Rampling, T; Powlson, J; Morter, R; Wright, D; Hill, A; Ewer, K (MDPI, 2018)
Immunogenicity of T cell-inducing vaccines, such as viral vectors or DNA vaccines and Bacillus Calmette-Guérin (BCG), are frequently assessed by cytokine-based approaches. While these are sensitive methods that have shown correlates of protection in various vaccine studies, they only identify a small proportion of the vaccine-specific T cell response. Responses to vaccination are likely to be heterogeneous, particularly when comparing prime and boost or assessing vaccine performance across diverse populations. Activation-induced markers (AIM) can provide a broader view of the total antigen-specific T cell response to enable a more comprehensive evaluation of vaccine immunogenicity. We tested an AIM assay for the detection of vaccine-specific CD4+ and CD8+ T cell responses in healthy UK adults vaccinated with viral vectored Ebola vaccine candidates, ChAd3-EBO-Z and MVA-EBO-Z. We used the markers, CD25, CD134 (OX40), CD274 (PDL1), and CD107a, to sensitively identify vaccine-responsive T cells. We compared the use of OX40+CD25+ and OX40+PDL1+ in CD4+ T cells and OX40+CD25+ and CD25+CD107a+ in CD8+ T cells for their sensitivity, specificity, and associations with other measures of vaccine immunogenicity. We show that activation-induced markers can be used as an additional method of demonstrating vaccine immunogenicity, providing a broader picture of the global T cell response to vaccination.